Diseño de una red de fibra óptica gpon para proveer servicios convergentes en el sector San Martín de Porres Bajo del cantón Esmeraldas a través de la red CNT E.P. - Lien Benítez, Wanjing Solange (2016)
In this moment, the sector San Martin de Porres Bajo belonging to the city Esmeraldas, has internet connectivity service, fixed telephony and DTH television using traditional methods of transmission. However, transmission speeds and quality of service do not satisfy to the subscribers of the sector due to its inefficient service. For these reasons, it is proposed to migrate copper networks to fiber optic networks with the purpose of comply the requirements of subscribers. This titling project aims to design a transportation network and an access network with FTTH (Fiber to the home) technology in the sector San Martin de Porres Bajo of the city of Esmeraldas of the province of the same name, using GPON (Gigabit Passive Optical Network) through the technological infrastructure of the Corporación Nacional de Telecomunicaciones. In chapter 1, a study of the concepts that define the GPON-FTTH access networks is performed with emphasis on the technical characteristics and transmission standards in order to have a broader view of the fiber optic networks. Thus, demographic variables of the sector San Martin de Porres Bajo and installed telecommunications infrastructure in this zone is analyzed; once it had been made this analysis the design of the fiber optic network GPON FTTH is prepared to satisfy the requirements of the habitants of this sector. In Chapter 3, a results analysis is performed to determine whether the design of the network can provide converged services in this sector ensuring high transmission speeds and excellent quality of service; likewise, the probability of growth of the network GPON to close areas is determined.